2009
DOI: 10.1007/s10151-009-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of left-sided colonic emergencies: a comparison of US, UK and Australian surgeons

Abstract: The management of left-sided colonic emergencies varies depending on geographic location and degree of colorectal subspecialization. While the literature suggests that single-stage procedures are accepted and safe, the reasons for this variation are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…13 However, more recently, primary anastomosis has been reconsidered as appropriate for left-sided lesions, particularly if the proximal colon is not severely dilated and the patient is deemed to be "good risk." [14][15][16] Other studies, albeit retrospective reviews, have demonstrated similar rates of anastomotic leak and operative mortality between right-and left-sided segmental colectomies. 12,17 In these studies, surgeons used on-table lavage to decompress the colon when performing an anastomosis in a left-sided obstruction.…”
Section: Segmental Colectomymentioning
confidence: 93%
See 1 more Smart Citation
“…13 However, more recently, primary anastomosis has been reconsidered as appropriate for left-sided lesions, particularly if the proximal colon is not severely dilated and the patient is deemed to be "good risk." [14][15][16] Other studies, albeit retrospective reviews, have demonstrated similar rates of anastomotic leak and operative mortality between right-and left-sided segmental colectomies. 12,17 In these studies, surgeons used on-table lavage to decompress the colon when performing an anastomosis in a left-sided obstruction.…”
Section: Segmental Colectomymentioning
confidence: 93%
“…The use of on-table lavage seems to be preferred in surveys of surgeons performing resection with primary anastomosis for a left-sided obstruction. [14][15][16] This technique involves mobilization of the colon and its division proximal to the site of obstruction, with placement of the proximal bowel end into a basin or sleeve; an appendicostomy is created and a 16-Fr balloon catheter is inserted into the cecum, using a purse string suture at the appendix to secure the catheter. The colon is then flushed with multiple liters of saline until clear, at which point the catheter is removed, the appendicostomy closed, and the operation proceeds on to creation of a primary anastomosis.…”
Section: Segmental Colectomymentioning
confidence: 99%
“…Although considerable progress has been made with regard to surgical techniques and in pre- and postoperative patient care, morbidity and mortality rates for emergency colon surgery continue to range between 11-35% and 9-22%, respectively [14,15,16,17,18,19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%